Public awareness and quality of products as predictors of customer loyalty among consumers (West African Journal on Sustainable Development, 2024)
This study examined public awareness and quality of products as predictors of customer loyalty among consumers in awka metropolis. A total number of two hundred Consumers in Awka metropolis, Anambra state served as participant for the study. The advertising effectiveness measure, quality of products scale (QPS) and customer loyalty scale (CLS), were used to generate data. Three hypotheses were utilized for the study. The first hypothesis stated that public awareness will significantly predict customer loyalty at (β=.238, p
Keywords: Public awareness; quality of products; customer loyalty; consumers